UJI KARAKTERISTIK PEMBAKARAN CRUDE PALM OIL - MINYAK DIESEL DENGAN MENGGUNAKAN DROPLET - Maulana, Aziz; Mursadin, Aqli (JTAM ROTARY, 2022)
This study aims to find out and see the characteristics of combustion of crude palm oil and diesel oil using droplets, the characteristics observed are the flashpoint of a fuel at the lowest temperature (Flash Point), the time from the heater under the droplet until the fire ignites (Ignition delay time), burning time of each droplet (Burning rate) and measure the height of fire on the results of combustion. Variation of the mixture of fuel Crude Palm Oil and diesel oil namely 10% Crude Palm Oil and 90% Diesel Oil, 20% Crude Palm Oil and 80% Miyak Diesel, 30% Crude palm Oil and 70% Diesel Oil, 40% Crude Palm oil and 60% Diesel Oil, and 50% Crude Palm Oil and 50% Diesel Oil. The tool used is a combustion chamber designed by researchers, Crude Palm Oil, Diesel Oil, Thermocouple and others. The results of this study are the lowest flashpoint results obtained in the mixture of 10% crude palm oil has a lower flash point value of 97⁰C and the highest value in the 50% crude palm oil fuel mixture is 152⁰C, the result of Ignition Delay Time is the value the lowest in the crude palm oil mixture of 10% has an average value of 0.52 seconds while the highest value in the crude palm oil fuel mixture is 50%, the average value is 2.72 seconds, then the results of the Burning Rate are the lowest value in the mixture of ingredients crude palm oil fuel 10% the average burning rate is 3.36 seconds while the highest value in the crude palm oil mixture is 40%, the average burning rate is 4.4 seconds and the result of visualization of fire or flame height is the highest value from a mixture of 10% crude palm oil with a fire height of 71.18 mm while those with the lowest fire height in a mixture of crude palm oil 50% have a high flame 66.45 mm.